PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN VARIABEL CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MODERASI - Mukti, Arifin Hamsyah; Winarso, Beni Suhendra (Universitas Ahmad Dahlan, 2020)
The purpose of this study was to investigate effect of profitability and capital structure with variable corporate social responsibility as moderation. The sampling technique in this study using purposive sampling method. The type of data this research is quantitative research with data sources used in the study is secondary data. The result of this research that positively affects the profitability of the company’s value, capital structure does not affect the value of the company, CSR moderating influence on the value of the company’s profitability, and CSR does not moderate the affect of capital structure on firm value